Tanggung Jawab dan Akibat Hukum Notaris dalam Pembuatan Perjanjian Pengikatan Jual Beli Tanah dan Bangunan Berkaitan dengan Adanya Pemalsuan Dokumen - Wahyu Indarko; Anriz Nazaruddin Halim; Holilur Rohman (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Discussion on the responsibility and legal consequences of a notary in making a land and building sale and purchase agreement related to document falsification. The method used in this study is a normative legal research type, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The results of the study on the responsibility of a notary in making a land and building sale and purchase agreement related to document falsification show that the application of the law in the decision is in accordance with Law Number 30 of 2004 which stipulates that if a notary in carrying out his duties and positions is proven to have committed a violation, the notary can be subject to or given sanctions in the form of criminal sanctions, civil sanctions and administrative sanctions. Notaries are often also drawn as parties who participate in or assist in committing a crime, namely making, ordering to enter or providing false information into a notarial deed.